Impact of baseline C-reactive protein levels on the response to secukinumab in ankylosing spondylitis: 3-year pooled data from two phase III studies. Issue 2 (21st November 2018) - Braun, Jürgen; Deodhar, Atul; Landewé, Robert; Baraliakos, Xenofon; Miceli-Richard, Corinne; Sieper, Joachim; Quebe-Fehling, Erhard; Martin, Ruvie; Porter, Brian; Gandhi, Kunal K; van der Heijde, Désirée; ,
Abstract : Objective: To evaluate the magnitude of response to secukinumab treatment over 3 years in patients with ankylosing spondylitis (AS) grouped by baseline C-reactive protein (CRP) levels in a pooled study of two pivotal phase III studies: MEASURE 1 (NCT01358175 ) and MEASURE 2 (NCT01649375 ). Methods: This post hoc analysis pooled data from all patients with available baseline CRP in the two studies who received subcutaneous secukinumab 150  mg (approved dose; N=197) or placebo (N=195). Assessed efficacy endpoints included Assessments of SpondyloArthritis international Society (ASAS)20/40, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), BASDAI50, AS Disease Activity Score inactive disease and ASAS partial remission among patients grouped by baseline CRP based on central laboratory cut-off <5  mg/L (normal) or ≥5  mg/L (elevated) and a cut-off <10  mg/L or ≥10  mg/L. Results: At baseline, 36.5% (143/392) patients had normal and 63.5% (249/392) had elevated CRP. At week 16, ASAS20/40 response rates were higher for secukinumab versus placebo in normal (56.9%/34.7% vs 28.2%/7.0%; p<0.01/p<0.001) and in elevated (63.2%/42.4% vs 29.0%/15.3%; both p<0.0001) CRP groups. Improvement was reported for all outcomes (p<0.05) in both groups, except for ASAS partial remission in the normal CRP group, where a numerical difference 12.5% vs 2.8%, p=0.07) was observed. Similar trends of improvement were observed in the <10  and ≥10  mg/L groups across all efficacy outcomes at week 16. Treatment responses to secukinumab in all CRP groups further improved over 156 weeks. Conclusion: Secukinumab 150  mg demonstrated rapid and sustained efficacy in patients with AS irrespective of baseline CRP, with greater magnitude of response in patients with more elevated CRP.